Co-designing community-based digital innovations for Maternal and Child Health (MCH) - Coleman, Toshka (Department of Computer Science, 2025)
Digital MCH (Maternal and Child Health) interventions improve access to, and awareness of, maternal and child healthcare. These interventions, however, often fail to receive uptake as the project objectives do not always align with community needs. This is attributable, in part, to the top-down nature of digital MCH programs, in which health and ICT experts typically inform the approach to these interventions, and the parents and caregivers being targeted, are excluded from the design process. This project aims to address this by directly including caregivers in the design of digital MCH interventions. In this research, we worked with caregivers and community members from various low-income South African communities to ascertain their MCH concerns and prioritize them accordingly. The outcome of this engagement informed the development of a digital intervention aimed at addressing these priorities. This research was carried out in three core phases. Phase 1 involved conducting community interviews with community members to learn about their current MCH contexts, and their digital MCH challenges and priorities. In Phase 2, we conducted co-design workshops with community members to ideate solutions to the challenges identified in Phase 1. Finally, Phase 3 involved analysing the feedback from the workshops, and iteratively developing a digital intervention with feedback from community members. This study identified and explored community-informed MCH priorities in South African communities that were not previously prioritised in the HCI community. These included accessibility to MCH information, building parenting skills in early life, and improving maternal mental health. Between the more rural and urban settings, we identified and distinguished the different nuances of these priorities, which we discovered were influenced by culture, socioeconomic conditions, and varying degrees of community involvement. Furthermore, we discovered that the communities value “connectedness” above access when addressing their MCH-related needs. Informed by our community engagements, we developed a resultant digital innovation to improve access to digital MCH in low-income communities, which have since been deployed and used by community participants. Finally, we determined that co-design approaches for MCH in low-income communities can be very effective if the appropriate tools are put in place, such as Design Cards, local intermediaries, and facilitator training.